Global burden of disease from cyclist road injuries in youth and young adults aged 15–39 years, 1990–2021 - Zhou, Li; Han, Ying (Frontiers in Public Health, 2025)
BackgroundCyclist: individuals who ride bicycles as a mode of transportation or recreation. Cyclist Road Injuries (CRI): road traffic injuries sustained by cyclists, including collisions with motor vehicles, pedestrians, or other cyclists, as well as single-vehicle crash’s (e.g., falls or crashes without external collision). Detailed analyses of the global burden of CRI among youth and young adults aged 15–39 remain limited. This study evaluates the disease burden of CRI from 1990 to 2021 using Global Burden of Disease (GBD) 2021 data.MethodsAge-standardized incidence (ASIR), death (ASDR), and disability-adjusted life year (DALY) rates were calculated across 204 countries and 21 regions, stratified by socio-demographic index (SDI). Linear regression modeling estimated annual percentage changes (EAPC) to assess trends.ResultsGlobally, ASIR, ASDR, and DALY rates declined from 1990 to 2021 (EAPCs: −1.26, −0.38, −0.80). However, absolute numbers of death cases and DALYs increased by 26.63 and 11.19%, respectively. High-middle SDI regions had the highest ASIR (259.70) and DALY rate (53.77), while middle SDI regions showed the highest ASDR (0.68). East Asia exhibited the highest ASDR and DALY rates. Andean Latin America saw the largest increases (EAPCs: 0.85, 2.13, 1.43), whereas high-income Asia Pacific showed the most significant declines (EAPCs: −3.52, −6.37, −5.20).ConclusionDespite declining rates, CRI burden remains significant, particularly in high-middle and middle SDI regions like East Asia and the Caribbean. Andean Latin America showed rising trends, while high-income Asia Pacific achieved substantial reductions.